Linguistic Synergy of Nature and Science in Haibuna Skincare Branding: A Critical Multimodal Discourse Analysis - Malinda Joan Caesarla; Vivi Vellanita Wanda Damayanti (Journal of Literature Language and Academic Studies, 2026)
Purpose – This study aims to analyze the structural and conceptual synergy between natural elements and scientific terminology in Haibuna Skincare’s product branding through a critical multimodal discourse analysis approach.  Methodology – Utilizing a qualitative descriptive research design, this study examines the product names and visual packaging of Haibuna Skincare. The data were analyzed by integrating Critical Discourse Analysis (CDA) with a multimodal framework that evaluates textual data, visual iconography, and internal laboratory chemical formulation data. Findings –The findings reveal that Haibuna strategically employs morphosyntactic compounding processes to bridge the domains of nature and science within its nomenclature. These lexical choices are consistently validated by packaging iconography and active chemical ingredients, thereby establishing a credible "Authority of Evidence" for consumers. Novelty – This research offers a brand integration of linguistic analysis and cosmetic formulation chemistry within critical multimodal discourse, highlighting how scientific verification prevents marketing overclaims. . Significance – This study benefits cosmetic brand strategists, researchers in applied linguistics, and modern skincare consumers by demonstrating the importance of informational transparency and multimodal consistency in contemporary branding.